The dawn of Ga2O3 HEMTs for high power electronics - A review. (15th November 2020) - Singh, R.; Lenka, T.R.; Panda, D.K.; Velpula, R.T.; Jain, B.; Bui, H.Q.T.; Nguyen, H.P.T.
Abstract: Recently, there is a growing interest in Gallium Oxide (Ga2 O3 ) as a promising semiconductor material for intended applications in RF, power electronics, and sensors with high capabilities over existing technologies due to its excellent material characteristics like large bandgap, well-controlled doping, and availability of large size inexpensive substrates. Bulk crystals of monoclinic β -Ga2 O3 can be grown using melt growth techniques, which ensures large, uniform substrates with relatively low-cost per wafer as compared to GaN and SiC substrates which are usually grown using vapor growth techniques. A large critical field of β -Ga2 O3 is beneficial for improving the DC performance of high voltage rectifiers and metal oxide semiconductor field-effect transistors (MOSFETs) and facilitates further lateral scaling of FETs for improved RF performance. Band structure of β -Ga2 O3 indicates difficulty in p-type conductivity, so previously reported most of the β -Ga2 O3 MOSFETs have been depletion mode, although enhancement mode operations were also demonstrated using recess-gate and charge-trapping gate stack structure. The β -Ga2 O3 heterostructures have been widely reported using a high-quality epitaxial layer of β -(Alx Ga1−x )2 O3 after alloying Al with Ga2 O3 . The β -Ga2 O3 modulation-doped FETs (MODFETs) have shown two-dimensional electron gas (2DEG) density of ~10 12  cm −2 that form a good quality channel at the interface. Despite low room temperature electron mobility of around 180 cm 2  V −1 s −1, peak mobility of around 2800 cm 2  V −1 s −1  at 50 K was measured in the latest reported experimental work of β -Ga2 O3 MODFET. III-nitride based GaN high electron mobility transistors (HEMTs) have been widely used in high power electronics and have shown 2DEG density ~ 10 13  cm −2 and channel mobility of 2000 cm 2  V −1 s −1 . This paper gives a perspective of Ga2 O3 material towards making high electron mobility transistors (HEMTs) for a certain class of RF applications. Due to low in-plane lattice mismatch, a high-quality epitaxial layer of GaN and AlN have been grown on β -Ga2 O3 . Furthermore, due to the inherent polarization property of III-nitrides and large bandgap, higher 2DEG density ~10 13  cm −2 and large conduction band offset >1.5 eV can be expected in AlN/ β -Ga2 O3 heterostructure. The various defects in WBG devices and their effects on the reliability aspects are also addressed.